PERFORMANCE ANALYSIS OF THE ELECTRIC TROLLEY OF OXYGEN CYLINDERS BASED ON THE ROAD SLOPE - Costantinus Oei; Maran Gultom; Obet Takke Ranteallo; Thobby Wakarmamu; Marthen Liga; Endang Hartiningsih; Johni Jonatan Numberi; Akbar Silo (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2023)
The demand for efficient distribution of oxygen cylinders at Abepura Regional General Hospital (RSUD Abepura) has been steadily increasing due to the growing needs of staff members and patients who expect high-quality service within the hospital premises. In response to this demand, this study aims to propose a transportation system that is not only automated but also time-saving, with the ultimate goal of enhancing medical services in a more efficient, eco-friendly, and safe manner. One of the main challenges faced in the distribution process is the hilly terrain surrounding RSUD Abepura. The presence of these hills makes it difficult to manually distribute the heavy 72 kg gas cylinders, which is the current method employed at the hospital. To overcome this challenge, this research suggests implementing an innovative solution—an electric trolley—that can effectively facilitate the distribution and flow of oxygen cylinders at RSUD Abepura. The findings of this study conclusively demonstrate that the electric trolley is not only a suitable but also a convenient solution for the operators and medical staff involved in the distribution process. By utilizing the electric trolley, they can distribute oxygen cylinders without facing any hindrances posed by the uphill roads, ultimately resulting in significantly improved time efficiency and service effectiveness at RSUD Abepura.